Investment Feasibility Analysis Of Additional Transportation at Wholesale as A Business Development Strategy - Haq, Muhammad Dliaul; Hidayah, Wahid Nur (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
The wholesale business in Sidoarjo is planning business development by increasing its transportation fleet from 4 cars to 8 cars in an effort to equalize the distribution of bakery products in Bandung. The main objective of this business development plan is to increase product sales and customer satisfaction in receiving products because we see an increase in market demand that has not been accompanied by an adequate transportation fleet owned by these wholesalers. An investment feasibility analysis is carried out to prove whether investment in additional transportation fleets is feasible and developed or not. The analysis is carried out using a financial aspect and a marketing strategy approach. The results of the analysis state that the NPV is greater than zero, the net BCR value is greater than one, the IRR value is greater than the specified discount rate, and the PP figure corresponds to the end of the investment period, which proves that this investment is feasible to carry out or develop.